Pharmacokinetic and pharmacodynamic analysis of enteric-coated mycophenolate sodium: limited sampling strategies and clinical outcome in renal transplant patients - Sommerer, Claudia; Müller-Krebs, Sandra; Schaier, Matthias; Glander, Petra; Budde, Klemens; Schwenger, Vedat; Mikus, Gerd; Zeier, Martin (British journal of clinical pharmacology, 2010)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Therapeutic drug monitoring of mycophenolate mofetil is a promising tool for reducing acute rejection episodes after renal transplantation. • Limited sampling algorithms of mycophenolic acid in mycophenolate mofetil-treated renal transplant patients have been established. • Recently published study results indicate that the intensity of early drug exposure might determine the risk of acute rejection episodes. WHAT THIS STUDY ADDS • This study provides pharmacokinetic and pharmacodynamic data of mycophenolic acid in enteric-coated mycophenolate sodium-treated renal transplant patients. • Limited sampling algorithms are evaluated and a practical sampling strategy with five sampling time points within the first 4 h after oral drug intake is provided in renal transplant patients with combined immunosuppression consisting of enteric-coated mycophenolate sodium and ciclosporin A. • The association between pharmacokinetic and pharmacodynamic parameters and the risk of adverse events are evaluated. • Both pharmacokinetic and pharmacodynamic parameters contribute to optimized individual immunosuppression. AIMS Pharmacokinetic (PK) and pharmacodynamic (PD) monitoring strategies and clinical outcome were evaluated in enteric-coated mycophenolate sodium (EC-MPS)-treated renal allograft recipients. METHODS PK [mycophenolic acid (MPA)] and PD [inosine monophosphate dehydrogenase (IMPDH) activity] data were analysed in 66 EC-MPS and ciclosporin A (CsA)-treated renal allograft recipients. Adverse events were considered in a follow-up period of 12 weeks. RESULTS Analyses confirmed a limited sampling strategy (LSS) consisting of PK and PD data at predose, 1, 2, 3 and 4 h after oral intake as an appropriate sampling method (MPA r2= 0.812; IMPDH r2= 0.833). MPA AUC0-12 of patients with early biopsy-proven acute rejection was significantly lower compared with patients without a rejection (median MPA AUC0-12 28 µg*h ml−1 (7-45) vs. 40 µg*h ml−1 (16-130), P < 0.01), MPA AUC0-12 of patients with recurrent infections was significantly higher compared with patients without infections (median MPA AUC0-12 65 µg*h ml−1 (range 37-130) vs. 37 µg*h ml−1 (range 7-120), P < 0.005). Low 12-h IMPDH enzyme activity curve (AEC0-12) was associated with an increased frequency of gastrointestinal side-effects (median IMPDH AEC0-12 43 nmol*h mg−1 protein h−1[range 12-67) vs. 75 nmol*h mg−1 protein h−1 (range 15-371), P < 0.01]. CONCLUSIONS Despite highly variable absorption data, an appropriate LSS might be estimated by MPA AUC0-4 and IMPDH AEC0-4 in renal transplant patients treated with EC-MPS and CsA. Regarding adverse events, the suggested MPA-target AUC0-12 from 30 to 60 µg*h ml−1 seems to be appropriate in renal allograft recipients.
Gesehen am 14.09.2023